Effect of the UV-Irradiation on the Linear Optical Properties of Ni-Phthalocyanine Thin Film - Addnan H. Al-Aarajiy (Journal of Global Pharma Technology, 2019)
A thin film of Nickel-phthalocyanine has been deposited with a thickness of 250 nm on glass, prepared by thermal evaporation using the Edward E306A coating at room temperature Rt. The high vacuum pressure during evaporation was about 10-5 m bar. The distance between the boat and the substrate was fixed at 20 cm. at the evaporation method, where the study of spectral behavior and optical properties of thin films of Nickel phthalocyanine (NiPc) by irradiation with ultraviolet (UV) at different times 0,10,20,40 and 80 min respectively, where we noticed that an increase of irradiation time leads to an increase absorbance and decrease the energy band gap. The absorption spectra recorded in the range of 190-1100 nm wavelengths showed the existence of two absorption bands, Soret or B-band and Q-band. The UV-Vis spectra showed that thin films deposited on same substrate types have directly energy-gap. The energy gap values of the prepared thin films were calculated from Tauc equation.Keywords: Thin film, Metal, Nickel phthalocyanine, Energy gap, Thermal evaporation.